Perceptual versus institutional determinants of entrepreneurial entry. Issue 2 (3rd March 2020) - Amini Sedeh, Amirmahmood; Beck, Joseph; Forghani Bajestani, Mahdi
Abstract : Purpose: This cross-national study of entrepreneurship seeks to investigate the perceptual and institutional determinants of entrepreneurial entry. To do so, the authors distinguish between social and commercial entrepreneurial activities, taking the position that the concept of entrepreneurship is not a monolithic one. Design/methodology/approach: The authors construct a large cross-national data set and employ hierarchical linear modeling (HLM) to run a multi-level analysis on individual-level data from Global Entrepreneurship Monitor (GEM) and country-level data from Polity IV and GLOBE, representing 47 countries. Findings: Individuals' perceptual characteristics (i.e. perceived self-efficacy, opportunity perception, and fear of failure) and informal institutions in the form of supportive cultures impact social entrepreneurship more strongly than commercial entrepreneurship. On the other hand, the formal institution of the rule of law, specifically the protection of property rights, is more conducive to commercial entrepreneurship. Originality/value: The results of this study contribute to theory by illuminating the complicated relationships between environmental conditions, individual-level psychological factors, and entrepreneurial decisions. Furthermore, the authors' multi-level model contributes to a more detailed conceptualization of entrepreneurial entry by identifying institutional settings that facilitate commercial versus social entrepreneurship. The authors also clarify why commercial entrepreneurship and social entrepreneurship attract different types of individuals.